2014
DOI: 10.1007/s12576-014-0333-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-arrhythmic effect of diosgenin in reperfusion-induced myocardial injury in a rat model: activation of nitric oxide system and mitochondrial KATP channel

Abstract: This study was designed to investigate the anti-arrhythmic effect of diosgenin preconditioning in myocardial reperfusion injury in rat, focusing on the involvement of the nitric oxide (NO) system and mitochondrial ATP-dependent potassium (mitoKATP) channels in this scenario. After isolation of the hearts of male Wister rats, the study was conducted in an isolated buffer-perfused heart model. Global ischemia (for 30 min) was induced by interruption of the aortic supply, which was followed by 90-min reperfusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…preconditioning [18][19][20]. The mitoK ATP channel may also take part in the diosgenininduced anti-arrhythmic effect [21]. In our study, the nonspecific blocker of K ATP GLI, the mitochondria K ATP channel blocker 5-HD and the mitochondria K ATP opener DIAZ were applied to observe the effect of K ATP on the cardioprotection bestowed by CIHH.…”
Section: Discussionmentioning
confidence: 90%
“…preconditioning [18][19][20]. The mitoK ATP channel may also take part in the diosgenininduced anti-arrhythmic effect [21]. In our study, the nonspecific blocker of K ATP GLI, the mitochondria K ATP channel blocker 5-HD and the mitochondria K ATP opener DIAZ were applied to observe the effect of K ATP on the cardioprotection bestowed by CIHH.…”
Section: Discussionmentioning
confidence: 90%
“…Another important effect of the antioxidant diosgenin is its potential interest in the protection of cardiac cells from hypoxia-reoxygenation injury which can be mediated by ATP-sensitive potassium channels and through modulation of cell prodeath (Bax) and cell prosurvival (Bcl2, heme oxygenase 1, and Akt) molecules [7478]. …”
Section: Pharmacology: Recent Datamentioning
confidence: 99%
“…Another important molecule is the K ATP channel due to its cardioprotection in various types of cardiovascular diseases (Badalzadeh et al 2014, 2015, Waza et al 2014. In addition, accumulating evidence has revealed that DM has been associated with dysfunction of the cardiovascular K ATP channels (Weintraub 2003).…”
Section: Introductionmentioning
confidence: 99%